CW EPR POWDER SIMULATIONS USING SPIRAL-TYPE GRIDS - CRĂCIUN, Cora (Studia Universitatis Babeș-Bolyai Physica, 2015)
This paper compares two types of spiral grids from the point of view of their homogeneity and efficiency for CW EPR powder simulations. One grid is well-known in the EPR context and has a parameter-free analytical expression. The other grid has been defined for minimizing the potential energy of charged particles on the unit sphere and has an adjustable shape. The quality of EPR simulations produced by these spiral grids is analysed for a spin system S = 1/2, with different symmetry of the gyromagnetic matrix.